2018
DOI: 10.18520/cs/v115/i1/108-121
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Erosion in the Fragile Himalayan Ecosystem of Uttarakhand, India Using USLE and GIS for Sustainable Productivity

Abstract: In this study, we assess quantitative soil loss in the Himalayan ecosystem of Uttarakhand, India using universal soil loss equation and geographic information system. The analysis shows that about 359,000 (6.71%), 473,000 (8.84%) and 1,750,000 ha (32.72%) area is under moderately severe (15-20 tonne ha -1 year -1 ), severe (20-40 tonne ha -1 year -1 ) and very severe (40-80 tonne ha -1 year -1 ) soil loss respectively. It clearly indicates that about 48.3% area of the state is above the tolerance limit of 11.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The majority of the forest and grassland/openscrub lies with in the mountainous region of the state and are generally subjected to higher risk of soil erosion due to higher degree of slopes. However, these areas are also reported to have higher risk of soil loss through erosion due to higher degree of land slope and high rainfall and are subjected to frequent occurrences of landslides every year (Mahapatra et al, 2018).…”
Section: Soc Stock Under Different Landuse Systemsmentioning
confidence: 99%
“…The majority of the forest and grassland/openscrub lies with in the mountainous region of the state and are generally subjected to higher risk of soil erosion due to higher degree of slopes. However, these areas are also reported to have higher risk of soil loss through erosion due to higher degree of land slope and high rainfall and are subjected to frequent occurrences of landslides every year (Mahapatra et al, 2018).…”
Section: Soc Stock Under Different Landuse Systemsmentioning
confidence: 99%
“…Therefore, a concern for development of any watershed area through the management of soil resources is required for enhancing agricultural productivity. Mahapatra et al, (2018) reported that the Uttarakhand state is affected by moderate to severe soil erosion due to deforestation, human intervention, climatic instability and natural disasters and poses serious threat to agricultural productivity. Thus, the present study was undertaken to characterize and classify the soils of Bino-river watershed in Almora district of Uttarakhand in India for enhancing agricultural productivity and overall development of this hilly region.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly, 175 Mha (53%) [in which 150 Mha is deteriorates by water and wind erosion alone, which accounts a loss of about 5.3 Mt of sub soil per year and remaining 25 Mha is degraded by various gullies, ravines, shifting cultivation, salinity, alkalinity and water logging] of total geographical area is suffering from different deteriorating effects of soil erosion and land degradation (Singh and Panda, 2017). In Northern India, deforestation, burning, clearing and dibbling of seeds alone causes about 4.1 tonnes ha -1 yr -1 of soil material to roll down towards the foothills due to steep to very steep slopes (Mahapatra et al, 2018). More than 50% of total geographical area of country is degraded by soil erosion (Saha et al, 2018).…”
Section: Land Degradation Problems In Indiamentioning
confidence: 99%
“…Nearly, 69.6% (228.3 Mha) of total geographical area of country comes under dry lands, in which 36% of area is seriously degraded (Thomas et al, 2018a). Mahapatra et al (2018) indicated that about 48.3% area of Uttarakhand state of India is above the tolerance limit of 11.2 tonnes ha -1 yr -1 of soil loss. In addition, nearly 147 Mha is degraded by erosion, in which about 94 and 9 Mha land is degraded by water and wind respectively, and remaining is degraded by acidification, salinity, flooding and combination of them etc.…”
Section: Land Degradation Problems In Indiamentioning
confidence: 99%
See 1 more Smart Citation